1988
DOI: 10.1111/j.1468-0092.1988.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Drilled Holes in Later Neolithic Pottery

Abstract: Holes drilled after firing are an occasional occurrence in earlier prehistoric pottery, and are generally accepted as intended to enable repair of cracks or breaks by binding. It would seem reasonable to expect that rates of repair would be fairly consistent, but this is not the case with later Neolithic ceramics in southern Britain. There, drilled holes are more common in the Grooved Ware tradition than in the Beaker or Peterborough traditions, and it is suggested that this may be owing to the high symbolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The King Barrow Wood plaques were deposited with some formality in a pit that also contained sherds of Grooved Ware, and in this case it seems that it was the symbols themselves, rather than the medium that bore them, that were of importance. The same argument applies to Grooved Ware pots themselves, for petrological analysis demonstrates that they were rarely traded over any distance, although individual pots were often curated, to judge by the presence of repair-holes used to bind breaks together (Cleal 1988).…”
Section: Commemoration and Referencementioning
confidence: 94%
“…The King Barrow Wood plaques were deposited with some formality in a pit that also contained sherds of Grooved Ware, and in this case it seems that it was the symbols themselves, rather than the medium that bore them, that were of importance. The same argument applies to Grooved Ware pots themselves, for petrological analysis demonstrates that they were rarely traded over any distance, although individual pots were often curated, to judge by the presence of repair-holes used to bind breaks together (Cleal 1988).…”
Section: Commemoration and Referencementioning
confidence: 94%
“…Occasional breakage and repair of vessels tends to be seen as a random part of the natural cycle of pottery use in domestic contexts, which is why such features have received little attention. Acts of repair have been explained as a response to seasonality constraints to pottery production (Howard, 1981: 25), or linked to ceremonial contexts (Cleal, 1988). The relative rarity of repaired vessels in British prehistory suggests that pottery would not have been routinely curated, a practice probably reserved for specific vessels that could not be easily replaced (Cleal, 1988: 141-42).…”
Section: Biographical Connectionsmentioning
confidence: 99%
“…Similarly, the large number of holes in sherds of Grooved Ware appears to be related to repair of the vessels with now‐decayed organic material. The fact that this type of Neolithic ceramic is four times more likely to have such repair holes suggests efforts to preserve these particular types of vessel as heirlooms (Bradley 2002, 57; Cleal 1988). It can even be suggested that obvious repairs may have acted in the same way as patina, indicating age and an earlier ‘life’ or ancestry for the vessel.…”
Section: Veneration Of Artefactsmentioning
confidence: 99%